2023
DOI: 10.3389/fgene.2023.1152414
|View full text |Cite
|
Sign up to set email alerts
|

Identification and verification of ferroptosis-related genes in gastric intestinal metaplasia

Abstract: Background: Gastric intestinal metaplasia (IM) is the key link of gastric precancerous lesions. Ferroptosis is a novel form of programmed cell death. However, its impact on IM is unclear. The focus of this study is to identify and verify ferroptosis-related genes (FRGs) that may be involved in IM by bioinformatics analysis.Materials and methods: Differentially expressed genes (DEGs) were obtained from microarray dataset GSE60427 and GSE78523 downloaded from Gene Expression Omnibus (GEO) database. Differentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Some studies have shown reduced CD4 and CD8 T lymphocytes with advancements along the Correa cascade, suggestive of altered immune surveillance, but there have been variations in this trend [125][126][127]. Song et al profiled the immune environment using CIBERSORT to show that the proportion of regulatory T lymphocytes and undifferentiated (M0) macrophages was higher than normal controls, while the proportion of CD4 memory T lymphocytes and dendritic cells was lower [128]. The interaction of these cells with each other and IM warrants further investigation, as well as the intersection with the specific immune response to H. pylori [129,130].…”
Section: Microbiome and The Immune Landscapementioning
confidence: 99%
“…Some studies have shown reduced CD4 and CD8 T lymphocytes with advancements along the Correa cascade, suggestive of altered immune surveillance, but there have been variations in this trend [125][126][127]. Song et al profiled the immune environment using CIBERSORT to show that the proportion of regulatory T lymphocytes and undifferentiated (M0) macrophages was higher than normal controls, while the proportion of CD4 memory T lymphocytes and dendritic cells was lower [128]. The interaction of these cells with each other and IM warrants further investigation, as well as the intersection with the specific immune response to H. pylori [129,130].…”
Section: Microbiome and The Immune Landscapementioning
confidence: 99%